2019
DOI: 10.3390/e21050453
|View full text |Cite
|
Sign up to set email alerts
|

The Solutions to the Uncertainty Problem of Urban Fractal Dimension Calculation

Abstract: Fractal geometry provides a powerful tool for scale-free spatial analysis of cities, but the fractal dimension calculation results always depend on methods and scopes of study area. This phenomenon has been puzzling many researchers. This paper is devoted to discussing the problem of uncertainty of fractal dimension estimation and the potential solutions to it. Using regular fractals as archetypes, we can reveal the causes and effects of the diversity of fractal dimension estimation results by analogy. The mai… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 66 publications
(136 reference statements)
0
8
0
Order By: Relevance
“…Since the length of coastline cannot be effectively measured, Mandelbrot put forward the concept of fractal dimension [ 5 ]. Fractal dimension can be defined on the basis of entropy and correlation function [ 3 , 4 , 6 ]. It is actually the invariant quantity in scaling transform and thus a parameter indicating symmetry.…”
Section: Introductionmentioning
confidence: 99%
“…Since the length of coastline cannot be effectively measured, Mandelbrot put forward the concept of fractal dimension [ 5 ]. Fractal dimension can be defined on the basis of entropy and correlation function [ 3 , 4 , 6 ]. It is actually the invariant quantity in scaling transform and thus a parameter indicating symmetry.…”
Section: Introductionmentioning
confidence: 99%
“…Different combinations of fractal elements result in different fractal dimensions for the terrain. The spatial analysis of a site can be conducted by obtaining comparable fractal dimension values [43]. The current study compared the fractal dimension of the restored terrain of Sparkling Lake generated by combining fractal elements with the surrounding landscape terrain to determine whether the restored Sparkling Lake terrain is similar to the surrounding terrain and whether the combination form of fractal elements under this mode is appropriate.…”
Section: Combination Of Fractal Elementsmentioning
confidence: 99%
“…Fractal dimension characteristics can also be seen in artificial landscapes, such as terraces [29,30], artificial land use [31], building environments [32][33][34], traffic networks [35,36] and others. The practice of fractal geometry in landscape restoration of quarries, open-pit mines, and other damaged environments [37,38], as well as river shoreline restoration [39], urban skyline construction [40,41], urban spatial organization structure [42][43][44][45][46][47], and landscape restoration [11], has confirmed that the balance, congruence, and symmetry of fractal images enhance pleasure in perception and cognition. Therefore, any change in fractal dimensions may affect people's visual judgment and preference for a landscape [48][49][50].…”
Section: Introductionmentioning
confidence: 99%
“…Since real fractals often have more than one scaling process, a single fractal dimension is insufficient to characterize them. A set of comparable parameters is required, which is provided by the multifractal spectrum [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…The spatio-temporal evolution of urban morphology is a critical focus area within geography, but existing multifractal research is not extensive enough. Urban multifractal research can be classified into three spaces: real space, order space, and phase space [ 16 ]. Real space corresponds to the spatial subdivision of urban land [ 17 ], transportation [ 18 , 19 , 20 ], population [ 21 , 22 , 23 , 24 ], and other elements [ 25 ]; order space refers to the hierarchical subdivision of urban system [ 26 , 27 ]; and phase space corresponds to dynamic processes.…”
Section: Introductionmentioning
confidence: 99%